2013
DOI: 10.1186/1472-684x-12-41
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-related neuropathic pain in out-patient oncology clinics: a European survey

Abstract: BackgroundAlthough pain is frequently experienced by patients with cancer, it remains under-treated. The primary aim of this study was to estimate the prevalence of cancer-related neuropathic pain (CRNP) in patients with chronic pain who attended an outpatient clinic for standard care in Europe (irrespective of the reason or stage of the cancer). The secondary aims of this study were to characterise pain and cancer in patients with CRNP (including treatment) and to evaluate the usefulness of the painDETECT (PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 24 publications
(43 reference statements)
2
25
0
4
Order By: Relevance
“…A non-interventional, cross-sectional study conducted in five European countries, including the UK, estimated that 32.6% of outpatients experiencing chronic pain experienced cancer-related neuropathic pain (CRNP) [18]. This is consistent with estimates from international studies conducted in a variety of inpatient and outpatient settings that up to 39% of patients with cancer may experience pain with a neuropathic component [14].…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…A non-interventional, cross-sectional study conducted in five European countries, including the UK, estimated that 32.6% of outpatients experiencing chronic pain experienced cancer-related neuropathic pain (CRNP) [18]. This is consistent with estimates from international studies conducted in a variety of inpatient and outpatient settings that up to 39% of patients with cancer may experience pain with a neuropathic component [14].…”
Section: Introductionsupporting
confidence: 69%
“…The authors would like to thank Sarah Wensley, Pfizer Ltd and all the UK investigators (full list reported elsewhere) [18] for their contribution to the study and Sarah Bowen for her role in the statistical analysis. The authors were not compensated for their work on the manuscript.…”
Section: Acknowledgementmentioning
confidence: 99%
“…El único estudio publicado hasta la fecha en el que se aportan datos específicos sobre la prevalencia de DNO en población anciana (> 65 años) es el publicado por Garzón-Rodríguez et al 19 . Es un estudio observacional, multicéntrico europeo (Dinamarca, Alemania, Grecia, España y Reino Unido) realizado entre el 2010-2011 en pacientes oncológicos paliativos ambulantes.…”
Section: Epidemiologíaunclassified
“…In a recent European survey, the proportion of chemotherapy-induced NP (CINP) pain among other NCP types was 32.6% 47. There are several reports showing that CP and NCP were diagnosed and treated inefficiently 20,22,48.…”
Section: Cancer Pain Syndromes and Neuropathic Cancer Pain: Causes Anmentioning
confidence: 99%